"Community practices" and "communities of practice" in smelting technology by XRF analysis of Archaic bronze votive figurines in central Italy (6th – 5th centuries BC). (June 2020) - Fulminante, Francesca; Unavane, Mukund
Abstract: This study uses semi-quantitative methods to analyse the metal composition of small, schematic bronze figurines that were popular in central Italy during the 6 th–5 th centuries BC, a time of rapid political change. These finds have been extensively studied stylistically, and their typologies are well established; their chronologies, however, are still problematic. Broadly similar figurines were widely distributed in assemblages, suggesting a commonality of cultural and religious practices. There is potential for these objects to elucidate the interethnic, religious and cultural boundaries in central Italy during political transition of the 6 th–5 th centuries BC. Both stylistic and metallurgical differences between figurines from different sites can improve our understanding of cultural boundaries. Using X-ray fluorescence (XRF) analysis to explore the metal content of the figurines, this study suggests the possible existence of regional and/or ethnic variation in the smelting processes.